Soil-water characteristic curve for SPV 200 - Nurashikin, Muhd Ramli (2015)
Clays are one of the alternatives used in the management of wastes disposal at landfills. Clays act as environmental barriers around waste disposal site where they are used as liners and capping materials for landfills sites. The clay liners act as barriers to water and containment flow in landfills and other waste containment facilities. Clays are used because of its hydraulic properties that is the soil-water characteristic curve (SWCC). This study focuses on the laboratory tests to measure the water retention characteristics of SPV 200 Bentonite. Bentonites have been considered due to their low permeability, high sorption capacity, self-sealing characteristics, and durability in a natural environment. Standard soil tests were conducted to determine the physical properties of the SPV 200. Two available technique that are osmotic technique and vapor equilibrium technique (VET) were used to establish the suction-water content SWCC curves. The osmotic technique is related to the osmosis principle where the water and salt exchanged to achieve equilibrium. This technique measure the matric suction occurred in the clay specimens. The suction is induced by the PEG 20 000 solutions where the suction ability is determined by the concentration. In VET, the clay specimen of SPV 200 are placed in closed thermodynamic environment containing aqueous solution of given alkaline salt solutions. Water exchanges occur by vapor transfer between the salt solution and clay specimen. Suction is applied to specimen when vapor equilibrium is achieved. The graphs of water content over varying suctions and water content over elapsed time are establish for each technique and then combine to show the curve of the drying process ranging from low suction to high suction value. In conclusion, SPV 200 bentonite has a swelling properties where it can absorb a lot of water and increase its volume, but when suction applied, the volume decreased as it experience a great loss in water content.